Code acquisition in coherent optical pulse CDMA systems utilizing coherent correlation demodulation. - Wei Huang (IEEE Transactions on communications)
A code acquisition technique based on active optical correlation detection is introduced for coherent optical pulse code-division multiple-access (CDMA) systems implemented through coherent correlation demodulation. Passive matched filter acquisition, commonplace in most radio CDMA systems, does not translate directly into the optical domain since synchronization between the incoming optical signal and a local optical code of the intended user at the receiver has to take place in several picosecond duration. Parallel and serial acquisition schemes under the same search algorithm are described and the effect of optical device noise, partial autocorrelation, and multiuser interference on acquisition performance is theoretically analyzed. Numerical results are given for Gold codes. In general, the degree of parallelism inherent in code acquisition techniques for radio systems allows a tradeoff between acquisition speed and hardware cost; however, in optical acquisition schemes, increasing the degree of parallelism with the concomitant hardware cost penalty does not necessarily reduce the time to acquisition. This is due to optical power budget limitations brought about by the need to split the optical signal, although optical amplifier technology can improve the performance of these parallel search schemes. The expressions for the partial correlation and multiuser interference derived in the paper can also be utilized for the analysis of other radio and optical acquisition schemes